Aggregate Supply and Demand Analysis - A Note on a 1963 Post Keynesian. Macroeconomic Textbook - Finn Olesen (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2007)
In the history of economic thought Post Keynesianism offers a different inter-pretation of John Maynard Keyness General Theory than what is known as mainstream Keynesianism. And at least in the Paul Davidson tradition of Post Keynesianism a direct connection to the writings of Keynes is present theoreti-cally as well as methodologically. This paper aims to present and to evaluate a textbook in Post Keynesian macroeconomics that Davidson wrote together with Smolensky in 1963.
Keywords: 330; Postkeynesianismus; Makroökonomik; Bibliometrie